Pelatihan Dan Pendampingan Pemasaran Digital Bagi Umkm Di Kelurahan Cibaduyut Wetan Bandung - Wijaya, Marvin Chandra (Penerbit Goodwood, 2025)
Purpose: The purpose of the activity is to assist and train MSMEs, particularly food vendors, in adopting digital marketing platforms such as GoFood, GrabFood, and ShopeeFood. This aims to help them transition to digital selling, improve their business reach, and enhance their economic opportunities. Research methodology: The program utilized a combination of training sessions and hands-on mentorship to guide participants through the process of transitioning to digital sales platforms. Mentors offered personalized assistance throughout the process, ensuring participants could successfully navigate platform requirements, complete account setups, and activate their profiles for digital sales. Results: The program achieved significant success, with participants completing all the required training and mentorship activities. They successfully registered their businesses on digital platforms such as GoFood, GrabFood, and ShopeeFood, set up their stores, and began selling their products online. Conclusions: The initiative effectively facilitated the digital transition for food vendor MSMEs, empowering them to utilize online platforms for sales. This not only improved their technological capabilities but also opened new avenues for income generation, demonstrating the success of the program in addressing their digital marketing needs. Limitations: While the program achieved its objectives, several limitations were observed. Participants faced resource constraints, such as limited access to smartphones or stable internet connections, which hindered full participation. Contribution: The program made significant contributions by empowering MSMEs, particularly food vendors, to adopt digital marketing practices and enhance their market reach. Participants gained valuable digital literacy and technical skills.